Against Orthodoxy Social Theory and Its Discontents - Aronowitz, S.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2015)
The book contains groundbreaking and immersive essays on crucial 20th Century scholars on social theory, discussed and analyzed from a radical, critical theory perspective. Aronowitz provides his unique and lauded critical eye toward the leading thinkers of our age, crafting an immersive set of essays on radical thought.
Keywords: Philosophy; Political economy; Political theory; Political philosophy; World politics; Critical theory; History of Philosophy; International Political Economy; Political Theory; Political Philosophy; Political History; Critical Theory